Arbitraging the Basel securitization framework: Evidence from German ABS investment - Matthias Efing (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
This paper provides evidence for regulatory arbitrage within the class of asset-backed securities (ABS) based on individual asset holding data of German banks. I find that banks operating with tight regulatory constraints exploit the low risk-sensitivity of rating-contingent capital requirements for ABS. Unlike unconstrained banks they systematically pick the securities with the highest yield and the lowest collateral performance among ABS with the same regulatory risk weight. This reaching for yield allows constrained banks to increase the return on the capital required for an ABS investment by a factor of four.
Keywords: G01; G21; G24; G28; 330; Regulatory arbitrage; asset-backed securities; reaching for yield; credit ratings